The Effectiveness of the Tapera Program in Improving the Welfare of Government Employees: Media Ethnography Analysis - Sintia Nur Afifah; Muhammad Aras Prabowo; Asiroch Yulia Agustina; Muhammad Ashlyzan Razik (Innovation Business Management and Accounting Journal, 2024)
The Public Housing Savings Program (Tapera) is an Indonesian government initiative to improve the welfare of the community, especially government employees, by providing access to affordable housing. Even though it has been running for several years, the effectiveness of this program is still being debated. This research aims to analyze the effectiveness of implementing the Tapera Program in improving the welfare of government employees. The research gap phenomenon that is the background for this research is the gap between program objectives and the reality of its implementation, such as low levels of participation and problems in financial management. The research method used is an ethnographic media study, by analyzing online news and discussions related to the Tapera Program. The research results show that although the Tapera Program has great potential in improving the welfare of government employees, its implementation still faces various challenges that need to be overcome to increase its effectiveness.